ChemInform Abstract: Protons and Hydroxide Ions in Aqueous Systems. Issue 38 (September 2016) - Agmon, Noam; Bakker, Huib J.; Campen, R. Kramer; Henchman, Richard H.; Pohl, Peter; Roke, Sylvie; Thamer, Martin; Hassanali, Ali
Abstract: Review: 253 refs.